Developing the router workshop [ - Sutton, Roy (Teach yourself woodwork, 1995)
Produced to aid those enthusiasts who wish to exploit their router to its full potential, featuring profile scribing for cabinet doors, panel raising, biscuit jointing, dovetailing, finger jointing, the ellipse jig, the routher lathe, the router carver, the pivot frame jig, and holding devices for special joints such as mitred corner joints.